Relasi Ayat ‘Am dan Khas: Antara Praktik dalam Perkara Thalaq dan Transformasi Hukum Keluarga Islam di Indonesia - M. Alhafis; Muhammad Alfin; Hendri Sutia Siregar; Muhammad Taufiq (AHKAM, 2025)
This study examines the interpretation of ayat ‘am (general) and khas (specific) in the Al-Qur’an related to thalak (divorce) and its relevance for the renewal of Islamic family law in Indonesia. The background of the study lies in the existence of divergent interpretations of divorce verses, which often influence the application of family law in contemporary social and legal contexts. The research aims to analyze the meaning of ayat ‘am and khas on thalak based on tafsir and uṣūl al-fiqh approaches, and to explain their implications for developing a more just and contextually responsive family law in Indonesia. This qualitative library research employs thematic exegesis (tafsīr maudhu‘ī), an uṣūl al-fiqh perspective, and a juridical-normative approach. Primary data are drawn from Al-Qur’an verses on thalak (Q.S. al-Baqarah: 229–230; Q.S. at-Talaq: 1–2), classical tafsir works, and foundational legal literature, while secondary data are obtained from books, journal articles, and regulations on family law in Indonesia. The findings show that ayat ‘am provide general principles of divorce, whereas ayat khas regulate the procedures and ethics of its implementation in more specific terms; an integrative interpretation of both yields a legal construction that balances normative and practical dimensions. Within the context of Indonesian family law, these principles support legal reform aligned with maqāṣid al-syarī‘ah, particularly the values of justice (‘adl), public welfare (maṣlaḥah), and the protection of human dignity. Accordingly, the interpretive framework of ayat ‘am and khas on thalak can serve as a conceptual foundation for strengthening Islamic family law in Indonesia so that it becomes more adaptive to contemporary developments while remaining firmly rooted in Al-Qur’anic values.